HUBUNGAN UMUR DAN FAKTOR PREDISPOSISI DENGAN INFEKSI SALURAN KEMIH PADA PASIEN RAWAT INAP DI RSUP H. ADAM MALIK MEDAN - Ginting, Hana Isal Salina (Deli Medical and Health Science Journal, 2025)
Urinary tract infections (UTIs) are often found in hospitalized patients, with several health conditions potentially playing a role. This study explores whether factors like age, diabetes (DM), HIV, kidney issues, and autoimmune diseases are linked to UTIs in patients at RSUP H. Adam Malik Medan. Methods, Using a cross-sectional design, data were gathered from 59 UTI patients in the hospital. Researchers reviewed their age and health status—including DM, HIV, kidney disease, and autoimmune conditions—and used Chi-Square and Fisher’s Exact tests to check for any associations. Results, No significant connections were identified between UTIs and any of the examined factors, including age (p=0.869), DM, HIV, kidney disease, or autoimmune disorders. The presence or absence of these conditions did not notably affect UTI occurrence. Conclusion, This study found that common risk factors like age and certain chronic diseases do not significantly impact UTI rates among patients in this hospital. These insights can help guide future UTI prevention efforts in clinical settings.